Effects of customized foot orthoses on lower limbs kinematics in adults with highly pronated foot - Permsombat, Pimwadee; Pensri, Praneet (Chulalongkorn Medical Journal, 2021)
Background: Previous studies have assumed that pronated foot may cause mechanical deviations of the lower limbs. Foot orthoses have been used for management to elevate the arch of the foot and alter the kinematic variables during walking. Objective: The purpose of this study was to examine changes in lower limb kinematic variables during the subphases of the gait stance of individuals with highly pronated foot after wearing customized foot orthoses (CFO). Methods: Thirteen adults (five women and eight men, average age 23.3 3.0 years) with asymptomatic highly pronated foot were included in the study. Participants with Foot Posture Index (FPI-6) scores between 10 to 12 were recruited. Changes in the kinematics of lower limbs in the stance period were measured using an eightcamera motion analysis system (Motion Analysis Corp., Santa Rosa, CA). All participants walked at self-selected speeds over a 10-meter walkway with three force platforms in two conditions between barefoot (BF) and wearing CFO. Statistical analysis was performed by Wilcoxon signed-rank test for selected rearfoot, ankle, knee and hip kinematics in a 3 dimensional gait cycle. Results: The important effects of CFO were seen in the initial contact phase (ICP) for ankle (P = 0.028) joint excursion, the forefoot contact phase (FFCP) for rearfoot (P = 0.001), ankle (P = 0.002), and hip (P = 0.039) joint excursions, the footflat phase (FFP) for ankle (P = 0.002) and hip (P = 0.003 - 0.046) joint excursions as well as the forefoot push off phase (FFPOP) for ankle (P = 0.003) joint excursion. Conclusion: These findings demonstrate the immediate effect of CFO for promoting good alignment of the rearfoot, ankle and hip joint excursions during walking among individuals with highly pronated foot.